2007
DOI: 10.1097/01.sap.0000248141.36904.19
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Surgical Treatment of Severe Cherubism

Abstract: Cherubism is an autosomal-dominant syndrome characterized by excessive bilateral maxillomandibular bony degeneration followed by fibrous tissue hyperplasia. Eight patients (age, 6-15 years; mean, 11 years) with severe cherubism were treated with a 2-stage operation by the same senior surgeon (C.M.R.-A.) over an 18-year period, 1987 through 2005. Severity was based on a modified Motamedi classification system. The diagnosis was established clinically, radiographically, and histologically. Postoperative follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 20 publications
0
51
0
4
Order By: Relevance
“…Curettage was the dominating procedure in reports based on larger clinical studie [8,17]. Cherubism is known to be a hemorrhagic lesion, Raposo-Amaral et al [6] reported an extensive resection was performed in two stages to prevent excessive blood loss in 8 children age 6 to 15 years old with severe cherubism. Henry.F et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curettage was the dominating procedure in reports based on larger clinical studie [8,17]. Cherubism is known to be a hemorrhagic lesion, Raposo-Amaral et al [6] reported an extensive resection was performed in two stages to prevent excessive blood loss in 8 children age 6 to 15 years old with severe cherubism. Henry.F et al…”
Section: Discussionmentioning
confidence: 99%
“…Usually The first signs of the disease appear between 1 and 3 years of age [4]. Motamedi [5] proposed a grading system for cherubism in 1998 which was modified by Raposo-Amaral et al [6] in 2007 (Table1). The authors in this article are reporting a case of a 23-year-old male patient with bilateral swelling of the lower jaw which was diagnosed with cherubism grade I class 5.…”
Section: Introductionmentioning
confidence: 99%
“…It is a self-limited disease, and some cases of spontaneous regression have been reported. Approximately 250 cases of cherubism have been reported, but, to the best of our knowledge, only 11 papers describe an orbital involvement [1][2][3][4][5][6][7][8][9][10][11] and only 4 [12][13][14][15] on rehabilitation with dental implants. * Corresponding author at: Ctra Colmenar km.…”
Section: Introductionmentioning
confidence: 99%
“…On retrouve au niveau odontologique des anomalies de nombre, de forme, d'érup-tion, des résorptions radiculaires. La classification de Motamedi, modifiée par Raposo-Amaral, établit la gravité des atteintes [7][8]. L'évolution histologique de la maladie a été décrite par Chomette [9] en trois phases : phase ostéolytique pendant l'enfance, phase de réparation conjonctive à la puberté, puis réparation osseuse.…”
Section: Introductionunclassified